Scientific journals:: form, content and indexing - Silveira, Aline Oliveira; Bahmad Júnior, Fayez (Revista Gestão & Saúde, 2017)
Ensure thestandard form and content of technical and scientific publications of the country is, since 1985, the mission of the Association of Medical Editors (ABEC). Therefore hasan important rolein the development and consolidation of publications of national scientific journal sthrough the exchange of idea sin systematic discussion forum son issues related to improving the quality of Brazilian scientific journals. Therefore, the ABEC conducts a periodic seminars, conferences and courses focused on academic publishing, disseminating knowledget o face the challenges of the publication to the demands of national and international scientific community.